Doing peace the rights way : essays in international law and relations in honour of Louise Arbour / edited by Fannie Lafontaine, François Larocque. - Lafontaine, Fannie; Larocque, François (François J.) (Intersentia, 2019)
With a foreword by former UN Secretary General Kofi Annan. This collection of essays addresses the most pressing contemporary issues in international law and relations. The authors are leading experts and renowned actors on the international stage, or in national jurisdictions, who have all interacted closely with Louise Arbour in the course of her career. Louise Arbour has had a profound impact on the development of international law and has played significant roles in international institutions, as Prosecutor for the International Criminal Tribunals for Rwanda and the former Yugoslavia, United Nations High Commissioner for Human Rights, CEO of the International Crisis Group and Special Representative of the UN Secretary-General for International Migration. She also held the top legal positions in Canada and helped shape Canadian law, as an academic and as a judge, sitting on its highest bench, the Supreme Court of Canada. Louise Arbour is a leader on issues of conflict prevention and resolution, criminal justice and human rights, and her vision often sets the standard. This unique collection of essays by world leaders and experts tackles substantive topics, such as the right to truth, torture, immunity and women's rights, in light of current and past events, challenging basic assumptions and bringing fresh thoughts to debates that are at the core of the world's agenda. The backbone of each contribution is the interaction between justice and peace, between human rights and conflict, and between law and politics, in the international sphere or domestic context. Doing Peace the Rights Way gathers together great minds, in honour of a true champion and ambassador of justice and human rights, in the hope that their vision on the most urgent debates of our time can help in getting us closer to the ideals of peace and justice for all. With contributions by Andrew Clapham, William Schabas, Tity Agbahey, Gilles Olakounlé Yabi, Alana Klein, Hina Jilani, J. Michael Spratt, Pablo Espiniella, James K. Stewart, Mona Rishmawi, Lisa N. Oldring, Fannie Lafontaine, Luc Côté, François Larocque, Tim McCormack, Fabrizio Hochschild, Philip Alston, Antonia Potter Prentice, Camille Marquis Bissonnette, Kim Pate and Natasha Bakht.